تقييم فاعلية بعض الصادات الحيوية في منع التصاق بعض أنواع الجراثيم المعزولة من الغلاف الحيوي(Biofilm) in vitro - عبد العزيز, فهيم; الأمير, لينة; العيسى, بشرى (Latakia University Journal -Biological Sciences Series, 2017)
يهدف البحث إلى تقييم فاعلية بعض الصادات الحيوية في منع التصاق بعض الأنواع الجرثومية المعزولة من الغلاف الحيوي (Biofilm) المتشكل في أنظمة مناهل بعض مزارع الدجاج البياض ودجاج اللحم(الفروُّج)، درست فاعلية خمس صادات حيوية (Fluoromphinicol،Erythromycin، Gentamycin ، Ciprofloxacin، Doxycycline) ضد ثلاث أنواع جرثومية هي ( المكورات العنقودية الذهبية Staphylococcus aureus ، الإشريكية القولونية Escherichia coli، العُطيفة الصائمية (Campylobacter jejuni وذلك باستخدام طبق المعايرة (المايكروتيتر) MTP، وتم قياس النتائج بجهاز(الإليزا) قارئ الميكروتيتر(UK) Microplate reader LT-4000 لقياس قيم الكثافة الضوئية Optical Density (OD) عند طول الموجة 630 نانوميتر.أظهرت النتائج وجود اختلافات متفاوتة في حساسية الجراثيم للصادات الحيوية المستخدمة، فكانت العنقودية الذهبية مقاومة لكل الصادات الحيوية المدروسة، وكانت أعلى فاعلية مع الدوكسي سايكلين (26.3%)، بينما كانت نتائج الجنتامايسين.2%) 15(، في حين لم يُبدِ الفلورومفينيكول فعالية واضحة في منع الالتصاق(1.8%)،أما الأرثرومايسين والسيبروفلوكساسين فقد كان تأثيرهما واضح في زيادة الالتصاق وتشكيل غلاف حيوي.بالنسبة لفاعلية الصادات المضادة لالتصاق الإشريكية القولونية والعُطيفة الصائمية كانت أعلى مع الفلورومفينكول إذ بلغت ((29.5% و((31.8% على التوالي وتناقصت فاعليته مع تناقص تركيزه (17.9%) و(23.5%)، أما الدوكسيسايكلين فقد كان تأثيره واضحاً في تحريض الجرثوم على زيادة الالتصاق وتشكيل الغلاف الحيوي بكل التراكيز. كما أظهرت النتائج وجود مقاومة للإريثرومايسين من قبل جراثيم التجربة، وارتفاع نسبة المقاومة مقابل كل الصادات الحيوية المدروسة باستثناء الفلورفينيكول الحديث الاستعمال، وتراجع في فعالية كل من الجنتامايسين والدوكسي سايكلين ضد الجراثيم السلبية لصبغة غرام (الإشريكية القولونية والعُطيفة الصائمية).The research aims to evaluate the efficacy of some antibiotics to prevent the biofilm formation by some isolated bacteria from biofilms in poultry watering systems in poultry farms (broiler flocks, laying hens) It had worked on three bacteria species, isolated from biofilm in poultry watering systems were Staphylococcus aureus, Escherichia coli and Campylobacter jejuni. We evaluated efficacy of five different antibiotics, fluorophinicol, Erythromycin, Ciprofloxacin, Gentamycin, Doxycycline. Bacterial identification and Disk diffusion test were carried out through standard procedures. Evaluation of the anti adherence efficacy of the antibiotics were carried out by using The microtiter plate assay and then the OD was measured at 660 nm using an ELISA reader. The results indicated the relative differences antibiotic resistance within the biofilm to different antibiotic. Staphylococcus aureus was resistant to all the studied antibiotics, the highest effectivenees with Doxycycline(26.3%) followed by Gentamycin (15.2%) in second place, while fluoromphinicol didn’t give clear effectivenss in preventing adhesion of bacteria(1.8%), either Erythromycin and Ciprofloxacin influence was evident in increased adhesion and forming the biofilm For effective antibiotics anti adhesion Escherichia coli and Campylobacter was higher with fluoromphinicol (29.5%), (31.8%) which decreasing effectivenss(17.9%), (23.5%). Either Doxycycline had clear impact on inciting the bacterium increased adhesion and formation the biofilm in all cconcentrations. The results also showed the presence of high bacterial resistance against and high resistance against to all the antibiotic except fluoromphinicol which new usage and Doxycycline in the effectivenss, and decreased effectivenss in each of Gentamycin against negative gram bacteria.